Embodiment, Religion, and Right-Wing Political Mobilisation: Charismatic Evangelical Women, Celebrity Pastors, and Electoral Politics in Brazil - Carpenedo, Manoela ca. 21. Jh. (Religion & gender, 2025)
Amid increasing violence during one of the most polarised election campaigns in Brazilian history, this article explores how Charismatic Evangelical women supported the far-right candidate Jair Bolsonaro in the 2022 elections. Drawing on virtual data produced by prominent religious influencers and pastors during the campaign, the article examines how these women use embodied religious practices in the public virtual sphere as a political act. The paper argues that this virtual space entertains and educates Brazilian Evangelicals about desirable cultural performances and serves as a pedagogical tool, teaching individuals how to perform conservative values and engage in embodied electoral mobilisation. Through religious practices such as prayer, fasting, and adherence to specific dress codes, Evangelical women combined religious devotion with bodily discipline in their support for Bolsonaro. This article contributes to understanding the rise of the Christian Right in Latin America and to broader debates about the significance of embodied practices in understanding the intersection of gender, religion, and electoral political mobilisation.